2003
DOI: 10.1152/ajpcell.00234.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading: biphasic osteocyte survival and targeting of osteoclasts for bone destruction in rat cortical bone

Abstract: Bone is removed or replaced in defined locations by targeting osteoclasts and osteoblasts in response to its local history of mechanical loading. There is increasing evidence that osteocytes modulate this targeting by their apoptosis, which is associated with locally increased bone resorption. To investigate the role of osteocytes in the control of loading-related modeling or remodeling, we studied the effects on osteocyte viability of short periods of mechanical loading applied to the ulnae of rats. Loading, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
219
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 343 publications
(236 citation statements)
references
References 49 publications
13
219
2
2
Order By: Relevance
“…This observation indicates that although both topography and mechanical stretching can induce similar bidirectional cell elongation, only mechanical loading, in excessive form, can activate apoptotic pathways [61][62][63][64].…”
Section: Discussionmentioning
confidence: 83%
“…This observation indicates that although both topography and mechanical stretching can induce similar bidirectional cell elongation, only mechanical loading, in excessive form, can activate apoptotic pathways [61][62][63][64].…”
Section: Discussionmentioning
confidence: 83%
“…Burr et al [45] showed that within 8 days of the introduction of fatigue microdamage in canine radii by in vivo flexural loading, osteonal Basic Multicellular Unit (BMU) resorption spaces are found in proximity to microcracks about seven times more frequently than would be consistent with random associations. Experiments performed in rats by [37,46] demonstrated that the time dependent migration of osteoclasts into regions of cortical bone containing experimentally induced microdamage have strengthened the argument for the targeting of damage in bone.…”
Section: Discussionmentioning
confidence: 99%
“…An elite sport with specificity of microfractures is well established particularly with sports such as running, gymnastics, and rowing (DiFiori et al, 2014). The osteocyte has been shown to undergo apoptotic death at sites of microdamage in bones and to release particular signals for bone destruction at this time (Noble et al, 2003, Kogianni et al, 2008. These signals remain to be identified but are of obvious interest to those in drug discovery for bone health.…”
Section: Osteocyte Biology Micro Damage and Stress Fracturesmentioning
confidence: 99%